Flotação por ar dissolvido na clarificação de águas com baixa turbidez utilizando sulfato de alumínio e sementes de Moringa oleifera como coagulantes - Lêdo, Patrícia Guilhermina da Silva (2008)
This work aims to investigate the process of Dissolved air Flotation (DAF) for clarifying water samples with low turbidity using aluminum sulphate and Moringa oleifera seeds as coagulants. The experimental procedure was carried out in a bench scale flotation unit. The influences on the pre-treatment conditions (coagulant dosage and flocculation time) and flotation parameters (superficial application rate and recirculation rate) were evaluated considering the efficiency of the process. The efficiency was evaluated by determining the turbidity of the untreated and treated water samples. The results obtained showed that turbidity reduction can be obtained very efficiently by using DAF and the latter coagulant in low turbidity water. Using aluminum sulphate in pH´s 5.0 and 6.0 better efficiencies were obtained with low concentrations (15 mg/L), achieving values of 92% of turbidity reduction. In the case of use of Moringa oleifera better efficiencies of reduction of turbidity were reported when using a concentration of 50 mg/L in all range of pH´s, achieving 86% of reduction. The zeta potential was also determined, in an attempt to aid comprehension of the coagulation mechanisms involved. The coagulation mechanisms with Moringa oleifera seeds were shown to be adsorption and charge neutralization, as well as adsorption and bridging. Concerning aluminum sulphate, the predominant mechanisms are adsorption and charge neutralization and enmeshment in a precipitate. The results indicate that for low turbidity water, Moringa oleifera seeds could potentially be a viable substitute for aluminum sulphate